(untitled) (Research, Society and Development, 2021)
Children undergoing cancer treatment have many symptoms and diseases that manifest themselves in an acute and chronic manner. The aim of this study was to carry out an integrative literature review on the following clinical question: Can cancer treatments (chemotherapy and radiotherapy) in children have oral repercussions? A search of scientific articles in the medline database was carried out, without the use of time limits. Publications made available in full and in English were considered. Of the 399 titles identified, 37 articles met the inclusion criteria and were included in the review. Eleven articles that did not meet the outcome or had closed access and no return from the authors were removed, finalizing 26 articles for the final study. There is significant evidence that children and adolescents experience numerous and complex symptoms and problems during and after cancer treatment. Diseases can be manifested during treatment as mucositis, ulcerations, xerostomia, caries and periodontal disease. For these diseases, the use of laser, orientation of fluoridated toothpaste and restorations should be performed to improve nutrition and health recovery and, in the long term, according to the dose, time and medication, the treatment promotes delay in the child’s growth, and consequently the time of tooth eruption and tooth anomalies. Therefore, understanding the trajectory of symptoms, based on the experiences of the child and family, is essential for comprehensive and sensitive care for children with cancer and their families, with the professional pediatric dentist being essential to monitor and treat these children until their adulthood.